Manejo de Cyperus rotundus con alternativas al bromuro de metilo en tomate de mesa - Gilreath, J.P.=700 1 Santos, B.M.
(Es, En)
Ilus., 15 ref.
Keywords: LYCOPERSICON ESCULENTUM; MALEZAS; CYPERUS ROTUNDUS; ESCARDA; HERBICIDAS; COSTA RICA; CLOROPICRIN; METAM SODIO; NAPROPAMIDA; PEBULATO